Caracterização das instalações, equipamentos, móveis e utensílios das unidades de alimentação e nutrição de creches municipais em Maceió/AL e sua relação com a presença e disseminação de fungos - cenário 2012-2013 - Gomes, Quitéria Meire Mendonça Ataíde (2014)
The fungi grows ubiquotously in the environment. That contaminants can be found in foods, being defined as mycotoxins. Generally, these have mutagenic e carcinogenic character, in which should be emphasized the high potential of aflatoxins. Despite the uncertainty of the manifestation of this potential, its mere existence justifies the use of all possible means to prevent it. This prevention can be done through the implement of good hygienic sanitary practice. The safety of foods compounds the Human Right of Adequate Foods (HRAF), because a healthy food does not have chemical, physical and biological contaminants, not being harmful to its consumers. The most vulnerable groups to Foodborne Diseases (FD) is composed of children from zero to six years old. . Should be noted that Brazilian law guarantees the social-educational attendance in day care centers and pre-schools to these children, and that this practice includes the provision of food. In this sense, the present study aims to evaluate the functional physical structures, observing the presence or absence of fungi, of Units Food and Nutrition (UFS) of municipal day care centers in Maceio, that serves children from zero to six years old. This assessment correlates with the Human Right to Adequate Food (HRAF). The dissertation is arranged in two parts. In the first, a review of the literature is made, in which are presented the characterization of pathogenic fungi, legal guidelines for food services and nutrition, and the relationship between childcare and DHHA. The second part consists of an exploratory cross-sectional study performed by analyzing the physical structure of the samples collected in twenty day care centers in Maceio. The evaluation of the sanitary aspects was made by applying a checklist prepared based on the RDC 216/04 of the National Agency for Sanitary Vigilance. From this checklist was given a score for the institutions observing the present or not accordant answers; and the missing or accordant answers. According to this score, the institutions were classified into three groups. Compounding the Group I, the daycare centers that attended 76-100% of the items, Group II, 51-75%, and Group III, 0-50%. In a (5.0) crèches, in refrigeration equipment there has been the growth of colonies, being the dominant genera Aspergillus, Candida, Penicilium, Histoplasma and Fusarium emphasizing the possibility of dispersing these pathogens that may compromise the health of children served in these environments. Candida spp. was found in 41 (25.60) of 160 plastic mugs reviewed and used by the children of zero to five years of age, probably resulting from the structural inadequacies and unsatisfactory sanitary hygienic conditions, which could favour the incidence of DOAs. The Spearman test was used to define the correlation between variables observed and the presence or absence of fungi in plastic mugs and the significance level adopted was of P < 0 .05. The results presented, being necessary investments in infrastructure and commitment of the actors involved in the management of these institutions, through the recruitment of an adequate number of professional nutritionists and food technologists established that the power supplied by the PNAE children 0 to 5 years, served on the municipal nurseries, has guaranteed food security.